Analisis Keamanan Transaksi E-Commerce Dalam Mencegah Penipuan Online - Purnama Ramadani Silalahi; Aisy Salwa Daulay; Tanta Sudiro Siregar; Aldy Ridwan (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2022)
Along with the development of the buying and selling transaction process, electronic fraud has also experienced an increase which has resulted in many consumers experiencing losses on transactions made due to fraud perpetrators in online transactions. This study aims to determine the effect of trust in conducting transactions in e-commerce related to the prevalence of fraud in e-commerce. This study uses a qualitative interpretive approach. This type of research is also known as phenomenological research, where this research presents phenomena that have interrelated patterns and meaning relations. Based on research in the field, the factors for the occurrence of fraud in e-commerce transactions include: minimal knowledge, wastage of virgins, tempted by fake gifts, high levels of hostility and poverty and government security policies that are less assertive. The forms of fraud in transactions on e-commerce include: phishing, pharming, pretexting, quid pro quo and contacting the victim directly